2020
DOI: 10.1093/jac/dkaa315
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and risk factors of multiple antibiotic resistance in patients who fail first-line Helicobacter pylori therapy in southern China: a municipality-wide, multicentre, prospective cohort study

Abstract: Background We aimed to study the prevalence of secondary antibiotic resistance of Helicobacter pylori in southern China and its risk factors, particularly geographical and socio-economic factors. Methods This was a municipality-wide, multicentre, prospective cohort study involving five major hospitals. Patients aged ≥18 years who failed first-line bismuth-based quadruple anti-H. pylori therapy between September 2016 and Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…The elderly population is more likely to be resistant to antibiotics because of excessive use in the past ( 91 , 92 ). A multicenter cohort study showed that people aged >40 years were particularly at risk of developing dual drug resistance to levofloxacin and metronidazole ( 93 ). In case of chronic infectious bronchial pneumonia in the elderly, it is important to be wary of levofloxacin resistance, as they may have already been treated with quinolones or fluoroquinolones ( 94 ).…”
Section: Treatmentmentioning
confidence: 99%
“…The elderly population is more likely to be resistant to antibiotics because of excessive use in the past ( 91 , 92 ). A multicenter cohort study showed that people aged >40 years were particularly at risk of developing dual drug resistance to levofloxacin and metronidazole ( 93 ). In case of chronic infectious bronchial pneumonia in the elderly, it is important to be wary of levofloxacin resistance, as they may have already been treated with quinolones or fluoroquinolones ( 94 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Therefore, sufficient first-time treatment is crucial. The rates of secondary resistance of H. pylori to multiple antibiotics may attributed to the high invasion phenomenon (Lyu et al, 2020). Our results of the comparative study indicated that some clinical strains have stronger invasive ability than standard strains, and the intracellular invasion may be a survival strategy of H. pylori because intracellular environments allow bacteria to avoid immune cells or exposure to antimicrobials (Thakur et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…In the elderly population with chronic respiratory or urinary tract infection, (fluoro)quinolone antibiotics are more commonly prescribed (Tandan et al, 2020). Lyu T et al (Lyu et al, 2020) showed that middle-aged and elderly patients had higher secondary resistance rates to metronidazole and levofloxacin in southern China. It is suggested to conduct drug susceptibility testing for H. pylori in the elderly population to select appropriate antibiotics.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%